1995
DOI: 10.1098/rspa.1995.0125
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of direct numerical simulation to understanding and modelling turbulent transport

Abstract: With the advances in large scale computers, reliable numerical methods and efficient post-processing environment, direct numerical simulation (DNS) has become a valuable and indispensable resource for fundamental turbulence research, although DNS is possible only when the turbulent Reynolds (or Peclet) number remains small to moderate. This paper reviews the contribution that various DNSS have made to understanding and modelling turbulent transport phenomena. After general remarks are made on the grid requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 74 publications
0
8
0
Order By: Relevance
“…Qualitatively, this is in line with literature; see, for instance, Refs. [10,11]. However, it should be noted here that |w h | is also affected by the geometry.…”
Section: Heat Fluxesmentioning
confidence: 88%
“…Qualitatively, this is in line with literature; see, for instance, Refs. [10,11]. However, it should be noted here that |w h | is also affected by the geometry.…”
Section: Heat Fluxesmentioning
confidence: 88%
“…For the case of strongest heating, near the heated wall, a saturation of the spanwise wavelength of the streaky system could be observed. Studies on turbulent channel flows by computations [24][25][26][27][28][29][30], and by experiments [31][32][33][34] have been carried out, since the earlier DNS [20] indicated that turbulent statistics along the wall bisectors agrees well with plane channel data despite the influence of the sidewalls in the former flow.…”
Section: Introductionmentioning
confidence: 93%
“…They found that the numerical simulation of TBLs is very sensitive to, e.g. proper inflow condition, sufficient settling length and appropriate box dimensions, and hence a DNS has to be considered as a numerical experiment governed by the chosen simulation set-up (Kasagi and Shikazono, 1995). For further progress in the investigation of these characteristics of TBLs, it is required the availability of accurate and reliable high-resolution DNS data for spatially developing TBLs with various numerical set-up such as inflow boundary condition, box dimensions and others.…”
Section: Introductionmentioning
confidence: 99%